The knowledge management capacity as an influencing element in the growth of production and continuity of organizations - Pazmiño Tamayo Estanislao M. (My University, 2023)
Companies are constantly faced with challenges, with their main concerns being production growth and staying competitive in an increasingly dynamic and integrated world. This research work aims to evaluate the influence of Knowledge Management Capability (CGC) on Production Growth (CP) and Organizational Continuity (CO), reflecting this capacity in the existing resources resulting from the various investments made by companies. This study was based on the ENESEM survey conducted by the INEC, which sampled 4, 324 ecuadorian companies from various productive sectors. It was developed using a quantitative, non-experimental, cross-sectional approach, employing the methodology of structural equation models with a transactional design. The research concluded that there are two variables of CGC in organizations that are related to CP, and four variables that are related to CO. These variables are significant in terms of maintaining a presence in the market. A pair of mathematical models were developed, which will enable an understanding of the different combinations of CGC variables required to achieve CP and CO.